The challenges of prenatal care services during the COVID-19 pandemic: qualitative evidence of primary health care providers’ perspective in Iran - Edris Kakemam; Faranak Karimiyeganeh; Farzaneh Soltani; Akram Karimi Shahanjarini (BMC Primary Care)
Abstract Background The COVID-19 pandemic affected almost all healthcare services, including prenatal care. Providing care to pregnant women during the pandemic was affected by general policies related to the control of COVID-19 and thus faced many challenges. Exploring the challenges of prenatal care during the pandemic can be helpful for effective planning and interventions to reduce the fundamental challenges. The present study aimed to explore the midwives’ perception of care challenges during the COVID-19 pandemic. Methods This qualitative research was conducted using conventional content analysis in 13 health centers of Hamadan, Iran, between July and September 2023. A semi-structured interview was conducted with 13 midwives who had experience providing prenatal care services to pregnant mothers during the COVID-19 pandemic and were selected using the purposive sampling method. Granheim and Lundman’s 5-step content analysis approach was used for data analysis. Results Three themes describing challenges to prenatal care during the COVID-19 pandemic emerged, including the unfamiliarity and unpreparedness of the health system in facing COVID-19, disruption in the quantity and quality of services, and socio-economic and systemic challenges. Conclusion PNC providers have experienced various challenges during the current COVID-19 pandemic. The results of the present study can be used to reduce the problems and challenges of providing prenatal care services in future pandemics. Effective interventions such as strong and managed organizational support, maintaining and sustaining the midwifery staffing, empowering PNC providers, supplying personal protective equipment, adopting strategies to improve mental health, and considering special measures and various incentives for midwives are necessary to overcome similar crises in the future.